MODEL KOMUNIKASI ANTI-RADIKALISME BERBASIS RAGAM BAHASA PERSUASIF, DIALOGIS, DAN HUMANIS, DALAM MENGURANGI KERENTENAN WACANA MASYARAKAT SERTA SINERGI BAHASA PARTISIPASI DAN COUNTER-NARRATIVE STRATEGY DALAM UPAYA SOSIALISASI BAHAYA RADIKALISME RUANG PUBLIK DIGITAL - Ahmad Riyadi; Andhika Fikri Ananda; Zalfa Hawwari Adhar; Sarah Nur Pauziah; Nurul Indah Lestari; Rezy Yulia Ramadhani; Sri Murniati (CV. Denasya Smart Publisher, 2026)
The digital world is currently highly vulnerable to the spread of radical ideologies packaged through sophisticated algorithms and deceptive emotional messages. This paper aims to design a new communication pattern that is more humanistic, engaging, and persuasive to protect the public from these negative influences. We use a mixed-methods research approach to thoroughly analyze field data and existing theories. The results show that an honest, open-for-discussion, and dignity-respecting approach is far more effective at breaking extremist narratives than simply banning content. In conclusion, combining engaging language styles with active citizen participation across various media platforms is the primary key to building strong community resilience on the internet.